2012
DOI: 10.1155/2012/278678
|View full text |Cite
|
Sign up to set email alerts
|

The Acute and Residual Effect of a Single Exercise Session on Meal Glucose Tolerance in Sedentary Young Adults

Abstract: The study goals were to (1) establish the variability in postprandial glucose control in healthy young people consuming a mixed meal and, then (2) determine the acute and residual impact of a single exercise bout on postprandial glucose control. In study 1, 18 people completed two similar mixed meal trials and an intravenous glucose tolerance test (IVGTT). There were strong test-retest correlations for the post-meal area under the curve (AUC) for glucose, insulin, and Cpeptide (r = 0.73–0.83) and the Matsuda i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
24
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(26 citation statements)
references
References 37 publications
1
24
1
Order By: Relevance
“…Lower carbohydrate intake before a GTT tends to produce higher values on the test 20 because insulin production tends to decrease when carbohydrate intake is lower. More physical activity 21 and lower perceived stress 22 tend to produce lower GTT values.…”
Section: Discussionmentioning
confidence: 97%
“…Lower carbohydrate intake before a GTT tends to produce higher values on the test 20 because insulin production tends to decrease when carbohydrate intake is lower. More physical activity 21 and lower perceived stress 22 tend to produce lower GTT values.…”
Section: Discussionmentioning
confidence: 97%
“…Short et al 20 and a test-retest correlation of 0.8 for repeated measurements with a coefficient of variation of 20%. Based on these values it was calculated that a sample of a minimum of 19 participants would be required for 90% power to detect a 5% difference (Cohen's d = 0.4, deemed a small-to-moderate effect) in Matsuda index between interventions at the 5% significance level.…”
Section: Methodsmentioning
confidence: 97%
“…While Short et al previously reported high MMTT reproducibility of a liquid test meal administered to healthy subjects [3], we employed the same test meal and operational techniques as the FNIH [1]. Since increasing study number observations can improve ICC precision [4], four men were recruited to undergo five-serial MMTTs over the course of one week.…”
Section: Examining Mmtt Reliability In Healthy and Overweight Menmentioning
confidence: 99%